PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Miftah, Miftah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is executed by because result learn the IPS expected by not yet reached the KKM specified by school namely 70. For that require to be done/conducted by a research with an eye to improve the result learn the IPS of student of class of IV SD Negeri 002 Jumrah Kecamatan Rimba Melintang. Tahaun Iesson 2014 / 2015 by applying model the study of co-operative of type NHT executed [at] March month;moon until April. Subjek in this research is student of class of IV SD Country 005 Sedinginan with the amount 25 student, 10 joe and 15 women. this Desain Research is Research of Class Action ( PTK). Pursuant to result analyse the data indicate that the result learn to experience of the improvement. At elementary score of mean assess 62,29 completely is klasikal 41,66% ( is not complete), mounting at cycle of I mean assess is 70,20 completely is klasikal 62,5% ( is not complete) and cycle II namely 84,16 completely is klasikal 91,66% ( tuntas).Selanjutnya of at activity learn and student also experience of the make-up of. Activity percentage learn at cycle of I meeting 1 that is 75% with the good category, meeting 2 that is 83,3% good category while at cycle of II meeting 1 that is 87,5% with the good category and meeting 2 namely 95,8% category very good. percentage of student Activity of at cycle of I meeting 1 that is 58,3% category less, meeting 2 namely 70,8% category enough while at cycle of II meeting 1 that is 83,3% with the good category and meeting 2 namely 95,8% category very baik.Dari of result of inferential research that with the applying model the study of co-operative of type NHTDAPAT improve the result learn the IPS of student of class of IV SD Negeri 002 Jumrah Kecamatan Rimba Melintang.Key Words : model the study of co-operative of type NHT, result of learning IPS, PTK